The implementation of the process approach to the writing of english essays in rural grade 12 classes in the Moroke Circuit - Dikgari, Ngokoana Magdeline (My University, 2011)
In 2008, the National Department of Education in South Africa introduced a new curriculum known as the National Curriculum Statement (NCS) in the Grade 12 classes. Prior to the introduction of this new curriculum, the writing of essays in Grade 12 classes was treated as a once-off activity. The focus on essay activities was mainly on the product and after the assessment of such product-driven essays, teachers had no further interest in them except for recording marks when necessary. The paucity of interaction between teachers and learners may have contributed to the majority of learners writing incoherent essays and achieving low marks. This research study investigates whether teachers in the Moroke Circuit understand and implement the process approach in the writing of English essays in rural Grade 12 classes as prescribed by the NCS. The NCS advocates the use of the process writing approach in essay writing. The process writing approach encourages a partnership between teachers and learners. Teachers are expected to treat learners’ essays as improvable objects through pre-writing activities, self and peer assessment which Kasanga (2004:64) refers to as “multiple-draft multiple-reader writing instruction”. To achieve the aim of the study, learners’ essays were checked against the process writing checklist and the teachers’ responses in the questionnaire they were requested to complete as part of the study. The findings revealed that teachers in the Moroke Circuit do not fully understand the process writing approach and thus they do not fully implement it as advocated. There are various factors which may contribute to the learners’ poor writing skills, the main of which appear to be the teachers’ inadequate training and poor understanding of the process writing approach. Some teachers attended short training courses on NCS and others did not attended any. Based on the findings, it is recommended that teachers should receive adequate training in the process writing approach for it to be implemented as effectively as the NCS prescribes.
Thesis (M.A. (English)) --University of Limpopo, 2011.
Keywords: Essays; English language; Essay -- Study and teaching; Creative writing (Secondary education)